2024
DOI: 10.1039/d3ta05147a
|View full text |Cite
|
Sign up to set email alerts
|

Fe-based dual-atom catalysts for the oxygen reduction reaction

Wuyi Zhang,
Shiyuan Yi,
Yihong Yu
et al.

Abstract: This review surveys Fe-based dual-atom catalysts for oxygen reduction reactions in next-generation energy devices, including challenges with single-atom catalysts, synthetic methods, catalytic performance, and future research directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Fe sites with low d-band centers facilitate easy desorption of terminally adsorbed OH* species from the active site. It can be found that the key factor for the alteration of the d-band center of metallic Fe atoms is due to the addition of N atoms that fundamentally modulate the electronic structure around the Fe_N x @BP system . These results confirm that the strong interaction between Fe atoms and coordination N atoms effectively accelerates the electron transfer, lowers the catalytic energy barrier, and improves the catalytic activity of the catalyst for ORR.…”
Section: Resultsmentioning
confidence: 65%
“…Fe sites with low d-band centers facilitate easy desorption of terminally adsorbed OH* species from the active site. It can be found that the key factor for the alteration of the d-band center of metallic Fe atoms is due to the addition of N atoms that fundamentally modulate the electronic structure around the Fe_N x @BP system . These results confirm that the strong interaction between Fe atoms and coordination N atoms effectively accelerates the electron transfer, lowers the catalytic energy barrier, and improves the catalytic activity of the catalyst for ORR.…”
Section: Resultsmentioning
confidence: 65%
“…3,4 However, oxygen reduction reaction (ORR), a critical electrochemical process within these devices, remains a bottleneck hindering their widespread adoption. 5,6 Therefore, the development of efficient ORR catalysts is essential to unlocking the full potential and accessibility of these sustainable energy systems. While Pt-based catalysts have traditionally dominated the field due to their outstanding catalytic activity, their high cost and scarcity have necessitated the exploration of alternative catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The escalating use of fossil fuels and their detrimental environmental consequences have spurred the development of renewable energy sources and innovative energy devices. , Among these advancements, metal–air batteries and fuel cells stand out as promising next-generation technologies due to their high energy density and minimal environmental footprint. , However, oxygen reduction reaction (ORR), a critical electrochemical process within these devices, remains a bottleneck hindering their widespread adoption. , Therefore, the development of efficient ORR catalysts is essential to unlocking the full potential and accessibility of these sustainable energy systems. While Pt-based catalysts have traditionally dominated the field due to their outstanding catalytic activity, their high cost and scarcity have necessitated the exploration of alternative catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…While substantial advancement has been made in fabricating SACs with enhanced catalytic performance through the incorporation of heteroatoms or nanoparticles into the surroundings of M–N 4 sites, the integration of multiple metal atom-sites to form DACs is still in its nascent stage. 17,18 However, challenges remain, as the electronic structures of many selected metal atoms for DAC construction (such as Fe/Mn, 19 Fe/Co, 20 Fe/Ni, 21 Fe/Cu, 22 Fe/Zn, 23 etc. ) are too similar, hindering the effective disruption of symmetrical charge distribution.…”
Section: Introductionmentioning
confidence: 99%